Investigation of the degradation of bio-recalcitrance in Apocynum venetum fiber biodegumming. Issue 1 (2nd January 2019) - Gong, Jixian; Zhang, Qiuya; Lou, Jiangfei; Zhang, Tao; Li, Huiqin; Li, Zheng; Li, Qiujin; Zhang, Jianfei
ABSTRACT: Traditional degumming of bast fibers results in problems such as environmental pollution and inferior fiber quality. For these reasons, biodegumming was considered as a potential process for bast fibers. In biodegumming process, decomposition of noncellulosic components was the pivotal problem. In this manuscript, the bast fiber of Apocynum venetum was processed with combinatorial processing, containing physical, chemical and microbial effect. The structural bio-recalcitrance was analyzed at molecular, supermolecular and morphological level in each stage. The results show that main substance in recalcitrance of Apocynum venetum bast is lignin and hemicellulose. And the protein and wax is also the constituent of bio-recalcitrance. The recalcitrance in the bast tissue can be divided into three layers. The spatial structure and the distribution of the noncellulosic substances also contribute to the recalcitrance. This paper provides directions for pretreatment design to render biomass more amenable to bioprocessing.